Digital marketing communication: a case study on the satisfaction level of the service of Roebuck Communications - Ashraf, Mohammad Zubayer (BRAC University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2018.